Bahasa SMS dari Segi Grafologis, Sintaksis, dan Psikolinguistik - Yetty Morelent (Fakultas Bahasa dan Seni UNP, 2011)
The widespread use of celular phones and SMS has spawned a variety of new word formation. These new words raise a language variety that leads to various interpretations. This is because the abbreviations and perpetuate sentences tend to